New Face(s) - Kenny, Carolyn; Stige, Brynjulf (Voices: A World Forum for Music Therapy, 2006)
We are proud to present this issue, Volume 6(1), with the new look that has been designed for the Voices Forum. Torgeir Stige, a young art student, has volunteered to produce a visual design that we think will suit the purpose and the function of Voices...